Pengangkatan Anak oleh Orang Tua yang Berbeda Keyakinan dengan Calon Anak Angkatnya - Fransiska Maryl Agatha; I Ketut Widia; I Ketut Sukadana (Jurnal Preferensi Hukum, 2020)
Adoption is a legal action to transfer custody of a child from a parent, legal guardian, or another person responsible for the care, education, and care of the child to the care of the adoptive parent. The adoption of children is generally carried out by married couples who cannot have children. Apart from a reproduction factor, there are a lot of other things encouraging adopting a child, one of them is compassion. This study aimed to examine the requirements for adoption based on PP. 54 of 2007 and the legal consequences of adopting children by adoptive parents of different beliefs from the prospective adopted children. This research is a normative legal research. Based on the results and discussion of this study, it was found that requirements for adoption based on PP. 54 of 2007 has been clearly regulated, and the detailed procedures and requirements for adoption have been regulated in Law No. 35 of 2014 concerning Child Protection with implementing regulations in the form of Government Regulation No. 54 of 2007 concerning the Implementation of Adoption and clear details in the Minister of Social Affairs Regulation No. 110 of 2009 concerning Requirements for Adoption of Children. In addition, adoption by prospective parents with different beliefs can be carried out by having a statement letter from the biological parents of the prospective adopted child stating that the child follows the beliefs of the adoptive parents. Whereas for homeless children a statement letter from the biological parents is made by the foundation or institution that accommodates the child.